The Influence of E-Service Quality and Website Quality on Purchase Decisions: The Role of Online Shopping Trust among Tokopedia Users - M. Willy Rekasiwi Rekasiwi; Ida Bagus Nyoman Udayana; Nonik Kusmua Ningrum (Amkop Management Accounting Review (AMAR), 2026)
This study examines the effects of e -service quality, website quality, and trust in online shopping on purchase decisions among Tokopedia users in Yogyakarta City. Although Tokopedia records high user traffic, its gross merchandise transaction value declined from 2022 to 2023, indicating a potential gap between platform visits and actual purchase decisions. The study employed a quantitative approach using a survey distributed through Google Forms to Tokopedia consumers who had made at least one purchase and were domiciled in Yogyakarta. A total of 144 responses were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression. The results show that e-service quality, website quality, and trust in online shopping have positive and significant effects on purchase decisions. In addition, e-service quality and website quality have positive and significant effects on online shopping trust. The regression model explains 60.8 percent of the variance in purchase decisions, while e-service quality and website quality explain 40.3 percent of the variance in trust. The key finding of this study is that trust in online shopping strengthens the role of digital service quality and website quality in shaping purchase decisions. These findings imply that Tokopedia and other e-commerce platforms should improve service reliability, website accessibility, information quality, transaction security, and consumer trust to increase purchase decisions.